2,3,9,10,15,16-Hexaazatetracyclo[6.6.2.04,16.011,15]hexadecane dihydrate - How, Fiona Ni Foong; Rahima, Z. A.; Tan, Yee Seng; Abdul Halim, S. Nadiah; Ng, Seik Weng (International Union of Crystallography, 2012)
The four six-membered fused rings in the title compound, C10H20N62H2O, adopt chair conformations; the H atoms of the four secondary N atoms occupy axial positions. Hydrogen bonds of the types N—H...N, N—H...O and O—H...N link the organic and water molecules into a three-dimensional network.